FTIR and Thermal Studies on Polyethylene Terephthalate and Acrylonitrile Butadiene Styrene - CHARLES, JULIE; RAMKUMAAR, G.R. (Asian Journal of Chemistry, 2010)
The present study deals with the characterization of the polymeric materials viz., polyethylene terephthalate (PET) and acrylonitrile butadiene styrene (ABS) by employing FTIR and thermal measurements. The complete vibrational band assignment made available for PET and ABS using FTIR spectra confirms their chemical structure. FTIR spectroscopy provides detailed information on polymer structure through the characteristic vibrational energies of the various groups present in the molecule. The thermal behaviour of PET and ABS essential for proper processing and fabrication was studied through TGA and DTA thermograms. The thermal stability of the polymers was studied from TGA and the activation energy for the degradation of the polymeric materials was calculated using Murray-White plot and Coats-Redfern plot. The polymer with high activation energy is more thermally stable. Polyethylene terephthalate is found to be more thermally stable than ABS. The major thermal transitions such as crystalline melting temperature (Tm) and degradation temperature (Td) of the polymers were detected from DTA curves. The melting behaviour of the polymer depends upon the specimen history and in particular upon the temperature of crystallization. The melting behaviour also depends upon the rate at which the specimen is heated. The various factors such as molar mass and degree of chain branching govern the value of Tm in different polymers.